Isolation of some species of fungi from fecal samples in Zawraa Park Zoo in Baghdad: Al‐Ameed Aseel I., Nagham M. Al‐Gburi. and Ammar Talib N. - I., Al‐Ameed Aseel (The Iraqi Journal of Veterinary Medicine, 2017)
Fecal samples were collected from eleven animal species, representing, different species. Samples were collected from cages before daily cleaning, in clean container, the sample was homogenized in tube contain sterile saline and kept for 30 min. and transferring 1 ml of the supernatant into Sabouraud Dextrose broth and incubate at 25-30˚C for two weeks, then 0.1 ml were seeded in Petri dishes containing Sabouraud Dextrose agar with chloramphenicol (50 mg/l). Results indicates high percents isolate for Geotrichum candidium (70.90%) of all animals, the high percents was from Porcupines, Kangaroos, Camels, and ponies (100%), followed by Wolves, Lamas, Dogs, Monkys, Mountain goats, Deers and Lions (83.33, 75, 66.66, 66.66, 50, 28.57 and 20)% respectively. The second high percent isolate was Rhizopus spp. (43.63%) reported in Porcupine, Kangaroo, Camels and Lions was 100% of isolates, followed by Pony (50%), Lama (33.33%), Deers (28.57%) and Monkys (25%). Also Aspergillus niger were isolates (3.63%), from Monkys (8.33%) and from deers (14.28%) while Aspergillus flavus isolates were (1.81) from Wolves (16.66%) and Fusarium spp. isolates (1.81%), from Wolves (16.66%). The results indicated that zoo animals may consider as a source of infection and transmission of fungi.